La multinationalisation des pétrolières canadiennes - Niosi, Jorge (L'Actualité économique)

(untitled) (HEC Montréal, 1984)
ABSTRACTCanadian foreign direct investment in the oil and gaz industry has been growing at a very rapid pace during the seventies and early eighties. Traditionnally oriented towards the United States, it is now flowring towards the United Kingdom and other North Sea Countries, the Mediterranean, Indonesia and Australia. Increasing oil prices and profits, mainly in international operations, explain the growth of many Canadian independent. These international firms are not already truly multinationals: they produce oil and/or gaz in two to four countries, but the extent of their exploration and development activities is leading them towards a more global activity.The article is organized into three sections. In the first section the patterns of ownership and control in the Canadian industry is shown, including the emergence of local companies and the "Canadianization" process of the seventies; in the second one, the multinational expansion of Canadian firms is analyzed using agregate data; in the final section the main results are summarized and some forecasts are made on the future evolution of Canada emerging oil multinationals.